2007
DOI: 10.1080/11358120709487708
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenols and Antioxidant Activity of Commercial and Wild Mushrooms From Chihuahua, Mexico Fenoles Totalesy Capacidad Antioxidante De Hongos Comercialesy Silvestres De Chihuahua, México

Abstract: Three wild edible mushrooms (Agaricus sp., Boletus sp., and Macrolepiota sp.) from the North of Mexico (Chihuahua state) and two commercial species (Agaricus bisporus white strain and Portabella: Agaricus bisporus brown strain) were analyzed to determine their proximate composition, total phenols and antioxidant activity. Wild mushrooms presented lower humidity values with respect to commercial species. Other proximate parameters such as total protein, lipids, ashes and carbohydrates were similar to those repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
(50 reference statements)
2
17
1
2
Order By: Relevance
“…[33] who found a high correlation between anti-oxidative activities and phenolic content concentrations which increased from 23.92%, 36.18% and 79.46% through increasing the concentrations from 100, 500 and 1000 mg/mL respectively. This result inconsistent with [34,35] regarding the relationship between antioxidative activities and phenolic content, the highest antioxidant associated with the greatest amount of phenolic content. Also, the reason for increasing the reducing power of secondary metabolites is probably due to reduced groups that interact with peroxides and prevent their formation [36e39].…”
Section: Discussioncontrasting
confidence: 79%
“…[33] who found a high correlation between anti-oxidative activities and phenolic content concentrations which increased from 23.92%, 36.18% and 79.46% through increasing the concentrations from 100, 500 and 1000 mg/mL respectively. This result inconsistent with [34,35] regarding the relationship between antioxidative activities and phenolic content, the highest antioxidant associated with the greatest amount of phenolic content. Also, the reason for increasing the reducing power of secondary metabolites is probably due to reduced groups that interact with peroxides and prevent their formation [36e39].…”
Section: Discussioncontrasting
confidence: 79%
“…The crude extracts for the determination of phenolics compounds and antioxidant activity were prepared according to Álvarez-Parrilla, de la Rosa, Martínez & González Aguilar, (2007). Dried samples (0.25 g) were mixed with 25 mL of 80% methanol and sonicated (Bransonic® CPX5800H) for 15 min.…”
Section: Preparation Of Extractsmentioning
confidence: 99%
“…In this sense, it has been reported that the stability of the antioxidant compounds of mushrooms (such as phenols) may be affected after harvesting, this due to enzymic and oxidative degradation, specifically phenol oxidases. [23] Alvarez-Parrilla et al [24] reported that this problem can be avoid by freeze drying, that prevent polyphenol degradation and minimize antioxidant activity loss, for instance, Agaricus sp., Boletus sp., and Macrolepiota sp. and two commercial strains of Agaricus bisporus (white and brown strain), [24] all wild edible mushrooms.…”
Section: Determination Of Antioxidant Capacitymentioning
confidence: 99%
“…[23] Alvarez-Parrilla et al [24] reported that this problem can be avoid by freeze drying, that prevent polyphenol degradation and minimize antioxidant activity loss, for instance, Agaricus sp., Boletus sp., and Macrolepiota sp. and two commercial strains of Agaricus bisporus (white and brown strain), [24] all wild edible mushrooms. Hence, freeze drying is an adequate process to maintain antioxidant activity and some compounds associated with this bioactivity.…”
Section: Determination Of Antioxidant Capacitymentioning
confidence: 99%